2018
DOI: 10.1002/ejoc.201801185
|View full text |Cite
|
Sign up to set email alerts
|

NHC‐Stabilized Radicals in the Formal Hydroacylation Reaction of Alkynes

Abstract: Mechanistic details of transformations catalyzed by N‐heterocyclic carbenes (NHC) are currently of great interest, targeting questions on the active catalyst in operation and the structure and reactivity of key intermediates. These mechanistic studies are driven by the need to understand the big impact of subtle changes on the catalyst system on its reactivity, as well as to clarify the situation around the elusive intermediates in the classical catalytic cycle. In the activation process of aldehydes the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These findings were consistent with a single‐electron transfer from the Breslow intermediate to the aldehyde substrate to give XI as an intermediate before the C−C bond formation. In a subsequent study, it was shown that the quantum chemically calculated and experimentally measured kinetics compare well, which provides further proof for this alternative mechanism. Accordingly, the mechanism established by Breslow can be extended by a radical pathway (Figure ).…”
Section: Alternative Reaction Mechanismsmentioning
confidence: 66%
See 1 more Smart Citation
“…These findings were consistent with a single‐electron transfer from the Breslow intermediate to the aldehyde substrate to give XI as an intermediate before the C−C bond formation. In a subsequent study, it was shown that the quantum chemically calculated and experimentally measured kinetics compare well, which provides further proof for this alternative mechanism. Accordingly, the mechanism established by Breslow can be extended by a radical pathway (Figure ).…”
Section: Alternative Reaction Mechanismsmentioning
confidence: 66%
“… Alternative reaction mechanism for the C−C coupling step of the benzoin condensation through a single electron transfer (Figure ) …”
Section: Alternative Reaction Mechanismsmentioning
confidence: 99%
“…The origin and reactivity of radical intermediates were analysed by EPR spectroscopy and supported by computational chemistry. This radical pathway was compared with the radicals observed in the benzoin reaction [45] …”
Section: Hydroacylation Of Sp Carbonmentioning
confidence: 99%
“…In addition to ionic-type (2-electron) mechanisms, thiazol-2-ylidenes have also recently become privileged organocatalysts for radical transformations of aldehydes. In these reactions, the Breslow-type enolates C – , which result from the condensation of aldehydes with NHCs in basic conditions, are able to undergo spontaneous single-electron transfer (SET) to challenging substrates ( E ox > −1.6 V vs SCE). In the absence of aldehydes, free NHCs are milder reducing reactants. For instance, imidazol-2-ylidenes perform stoichiometric reduction of the ferrocenium cation ( E = +0.38 V vs SCE) and the trityl cation ( E = +0.27 V vs SCE) .…”
mentioning
confidence: 99%